Determinant of Intention to Check-Up Back to Doctors at Public Hospital - ., Sedianingsih; Tri Ratnasari, Ririn; Prasetyo, Ari; Mawardi, Imron (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the factors that influence the intention to check up back if it pain to Dr. Soetomo Hospital and Hajj Public Hospital. This research was conducted with a quantitative explorative approach with an analysis design factors. The first stage of this research is exploring the factors that exist in the minds of patients with spreading open questionnaire, having acquired these factors, then the second phase of this study, carried out a survey to patient non BPJS outpatient and inpatient care in Dr. Soetomo Hospital and Hajj Public Hospital. The sampling technique is purposive sampling. Furthermore, the data were processed using factor analysis. The output of this study is an international journal. The results of this study indicate that factors that affect intention to return (check up back) if pain to Dr. Soetomo Hospital and Hajj Public Hospital formed by six factors. Factors that formed called the service factor, the factor of the facility, hospital image factor, the factor of interpersonal relationships, and location factors. Indicators with the highest loading values obtained from the calculation of the rotation factor is an indicator of the X6 in hospital image factor is the hospital that has the most complete medical equipment in the city of Surabaya.
Keywords: Factors and Intention to Check up Back If Patients have sickness.